Social responsibility and psychological capital among fisherfolks - Abagatnan, Samuel Delos Santos
The purpose of this study is is to describe fisherfolks level of social responsibility and psychological capital consisting of four factors: self-efficacy, resilience, hope, optimism, and to determine the relationship between them. Measures of social responsibility, self-efficacy, resilience, hope and optimism were administered to thrity-five fisherfolks (n=35) using an interview. Open-ended questions for optimism were also included. Results indicate that fisherfolks have high levels of social responsibility, self-efficacy and hope, and moderate levels of resilience and optimism. Self-efficacy, hope and resilience are not related to social responsibility. Only optimism among the four factors of psychological capital is related to social responsibility. The present study contributes information to fishers' positive attitude on life by looking at their self-efficacy, resilience, hope, optimism and sense of social responsibility, which previous literature unable to explore in detail.